The dynamic impact of green finance and renewable energy on sustainable development in China - Chen, Jiahui; Li, Lun; Yang, Dechun; Wang, Zuogong (Frontiers in Environmental Science, 2023)
Abstract: In recent years, sustainable development has become a focal issue in the globalization process due to environmental uncertainty in the global context, which has attracted the extensive attention of scholars. This study explores the dynamic transmission mechanism and time-varying impacts among green finance, renewable energy and sustainable development in China on the basis of a stochastic volatile time-varying vector autoregressive (TVP-VAR-SV) model using time-series data from January 4, 2013, to October 14, 2022. First, there is found to be an interaction among green finance, renewable energy and sustainable development in China, and the degree of influence and direction of action at different points in time show time-varying and heterogeneous characteristics. Second, this study subdivides renewable energy into hydro, wind, geothermal and solar energy. The dynamic impact of these types of energy on sustainable development is heterogeneous, and this relationship is affected by relevant economic events. In the process of promoting sustainable development in China, the findings of this study have theoretical and policy implications for the development and risk prevention of green finance and renewable energy markets in China.